Impact of coordinated capacity mechanisms on the European power market - Michael Bucksteeg; Stephan Spiecker; Christoph Weber (University of Duisburg-Essen, House of Energy Markets & Finance, 2017)
There is an ongoing debate on the introduction of capacity markets in most European countries while a few of them have already established capacity markets. Since the implementation of independent national capacity markets is not in line with the target of a pan-European internal electricity market we investigate the impacts of uncoordinated capacity markets compared with coordinated capacity markets. A probabilistic approach for the determination of capacity requirements is proposed and a European electricity market model (E2M2s) is applied for evaluation. The model simultaneously optimizes investments and dispatch of power plants. Besides the impact on generation investments, market prices and system costs we analyse effects on production and security of supply. While coordinated capacity markets reveal high potentials for cross border synergies and cost savings, uncoordinated and unilateral implementations can lead to inefficiencies, in particular free riding effects and endanger security of supply due to adverse allocation of generation capacity.
Keywords: 330; capacity markets; system adequacy; market design